The life of dragonflies: order Odonata - Pimenta, Paloma Cristina; Pelli, Afonso (Ciência e Natura, 2019)
The Odonata Order has a wide geographical distribution. The life cycle is complex, with stage of aquatic nymph, the naiad and winged adults. The research was carried out in peer-reviewed journals at the PuMed and Capes databases, with the keyword Odonata "and" ecology, when the text was complete and available. The used books were researched with insects theme, entomology, available in the collection of the library of the Federal University of the Triângulo Mineiro or private collection. The theoretical framework deals with biology, life cycle, sexual behavior and biodiversity. The Odonata order needs preserved places to reproduce and develop. Some authors mention that certain species of dragonflies can be considered good bioindicators of preserved environment, since they are sensitive to environmental changes. Finally, there is a need for further studies on taxonomy, physiology, and ethology to use this group as a bioindicator in quick works.